Available Evidence in Application of Paper Mulberry in Animals Breeding. Issue 2 (February 2020) - Du, Ruihuan; Zheng, Baiqin; Duan, Xiaoran; Xiang, Aili; Huo, Luman; Li, Aijun; Zhang, Guosheng; Dong, Lixue
Abstract: As a new protein feedstuff, paper mulberry has the characteristics abundant nutrition, high protein content and good palatability, and has great development potential. In this paper, the feeding value of mulberry, the feeding method and the application in animal feeding are reviewed, which provides reference for the wide application of mulberry in animals breeding.